Co–Cr–Mo alloy binding peptide as molecular glue for constructing biomedical surfaces. (June 2020) - Migita, Satoshi; Sakashita, Kosuke; Saito, Yuta; Suyalatu,; Yamazaki, Tomohiko
The mechanical properties of Co–Cr–Mo (CCM) alloys are advantageous in various biomedical applications. However, because of their bioinert surface, CCM alloys exhibit poor endothelial cell attachment properties; thus, problems of biocompatibility remain. In this study, we aimed to improve the biocompatibility of the CCM alloy surface using solid-binding peptides. We selected peptides with high binding affinity for cast CCM alloy surfaces through in vitro evolution by the phage display method. The peptides were functionalized on the CCM alloy surfaces by simple immersion in the peptide solution. The peptide bound to both cast and 3D-printed CCMs with the same affinity. The peptides linked to the amino acid motif that promotes cell adhesion, and improved the attachment of endothelial cells on the 3D-printed CCM in serum and serum-free conditions. Hence, CCM-binding peptides are attractive tools for constructing a biofunctional surface on CCM-based biodevices.